Symptomatic and incidental thromboembolism are both associated with mortality in pancreatic cancer - Menapace, Laurel A.; Peterson, Derick R.; Berry, Andrea; Sousou, Tarek; Khorana, Alok A. (Thrombosis and Haemostasis, 2011)
Pancreatic cancer is known to be associated with VTE, but contemporary rates of incidental and symptomatic VTE events and their association with mortality are incompletely understood. We conducted a retrospective cohort study of consecutive pancreatic adenocarcinoma patients at the University of Rochester from 2006–2009. Data were analysed using a Cox model with time-dependent covariates. A total of 1,151 radiologic exams of 135 patients were included. Forty-seven patients (34.8%) experienced VTE including 12 pulmonary emboli (PE), 28 deep-vein thromboses (DVTs) and 47 visceral vein events. Incidental events comprised 33.3% of PEs, 21.4% of DVTs and 100% of visceral VTE. Median (95% CI) conditional survival beyond three months was 233 (162–322) more days for those without VTE, which was significantly greater than 12 (3–60) days for those with DVT as first event (p<0.0001) and 87 (14–322) days with visceral first events (p=0.022). In multivariate analysis, DVT (HR 25, 95% CI 10–63, p <0.0001), PE (HR 8.9, 95% CI 2.5–31.7, p = 0.007) and incidental visceral events (HR 2.6, 95% CI 1.6–4.2, p =0.0001) were all associated with mortality, though anticoagulants reduced these risks by 70% (26–88%, p = 0.009). In conclusion, VTE occurs in over one-third of contemporary pancreatic cancer patients and, whether symptomatic or incidental, is strongly associated with worsened mortality. The role of anticoagulation in treating incidental or visceral VTE warrants further study.Note: The abstract of this manuscript was presented at the Annual Meeting of the American Society of Hematology, Orlando, FL, USA on December 5, 2010.
Keywords: Malignancy; hypercoagulability; imaging